Optimizing Digital Transition: Addressing Challenges in Modernizing Inventory Systems in Primary Healthcare Facilities - Bolaños, Jam Claudinee S.; Diaz, Yves Evita S.; Lalaguna, Jeseneth Danica A.; Malang, Bernandino P.; Philippines, Jocelyn DS. (Future Science / FSH-PH Publications, 2024)
This study investigates the challenges and potential solutions associated with modernizing inventory systems in primary healthcare facilities in the National Capital Region (NCR) of the Philippines, emphasizing operational efficiency, resource management and staff training. A descriptive research design was applied, using both quantitative and qualitative approaches. Data was collected from 67 trained staff members through purposive sam-pling, ensuring diverse perspectives across various organizational roles. The questionnaire was evaluated in relation to users' perceptions of satis-faction, operational efficiency, and the perceived difficulties with digital inventory systems. Reliability is established with the help of Chronbach's Alpha, and ANOVA, used in establishing the relationship between user sat-isfaction and operational effectiveness. From the thematic analysis of the questionnaire, lack of infrastructure, lack of training, and fractured supply chains were pointed out as being the obvious challenges that reduce the smooth digital transition. The study found that while digital transfor-mation has the potential to enhance inventory management and healthcare delivery, significant barriers must be addressed to achieve full adoption. Overall, findings help highlight the need for focussed training with strong digital solutions in optimizing resource management and service delivery in public health settings, providing valuable insights for policymakers and healthcare administrators.